Human resource management practices in building learning organizations: a study of large manufacturing organizations in Malaysia / Norashikin Hussein - Hussein, Norashikin (2013)
The rapidly changing business environment requires organizations to gain unique and sustainable competitive advantages over their competitors. Recognized as a source of competitive advantage, effective human resource management practices (HRM practices) clearly play a vital role in the success of any organization. As the knowledge economy demands for quality human resources, human resource management is called to play a more strategic role in facilitating learning in the organization, particularly in building learning organization. The objectives of this study are: (1) to examine the level of HRM practices in manufacturing organizations; (2) to investigate the relationships between HRM practices and building of learning organization; and finally (3) to examine leadership styles as moderator the relationship between HRM practices and building a learning organization. Based on the resource-based view theory, this study hypothesized that HRM practices would positively influence in the building of a learning organization. Data were collected using mail questionnaires sent to middle managers and nonexecutive employees of manufacturing organizations in Malaysia. A total of 150 useable responses were obtained and used for the purpose of analysis. Based on the mean scores, results revealed that HRM practices were highly practiced in the surveyed organizations. Results of multiple regressions indicate positive and significant relationships between performance-based pay, performance appraisal procedure, promotion and staffing on various learning organization dimensions. Hierarchical regression was utilized to test the impact of leadership styles as the moderating variables. Only management by exception (passive) leadership was found to partially moderate the relationship between HRM practices and building of learning organization namely for team learning and inquiry, embedded system and empowerment, and continuous learning. The other two moderators; transformational leadership and contingent reward leadership were found to have insignificant relationship between HRM practices and building a learning organization. The findings can form a basis for useful recommendations for top management and managers in tailoring HRM practices in promoting learning organization and further maintain their competitive advantage for long term organizational success.